Light-induced structural changes in a short light, oxygen, voltage (LOV) protein revealed by molecular dynamics simulations—implications for the understanding of LOV photoactivation - Bocola, Marco; Schwaneberg, Ulrich; Jaeger, Karl-Erich; Krauss, Ulrich (Frontiers in Molecular Biosciences, 2015)
The modularity of light, oxygen, voltage (LOV) blue-light photoreceptors has recently been exploited for the design of LOV-based optogenetic tools, which allow the light-dependent control of biological functions. For the understanding of LOV sensory function and hence the optimal design of LOV-based optogentic tools it is essential to gain an in depth atomic-level understanding of the underlying photoactivation and intramolecular signal-relay mechanisms. To address this question we performed molecular dynamics simulations on both the dark- and light-adapted state of PpSB1-LOV, a short dimeric bacterial LOV-photoreceptor protein, recently crystallized under constant illumination. While LOV dimers remained globally stable during the light-state simulation with regard to the Jα coiled-coil, distinct conformational changes for a glutamine in the vicinity of the FMN chromophore are observed. In contrast, multiple Jα-helix conformations are sampled in the dark-state. These changes coincide with a displacement of the Iβ and Hβ strands relative to the light-state structure and result in a correlated rotation of both LOV core domains in the dimer. These global changes are most likely initiated by the reorientation of the conserved glutamine Q116, whose side chain flips between the Aβ (dark state) and Hβ strand (light state), while maintaining two potential hydrogen bonds to FMN-N5 and FMN-O4, respectively. This local Q116-FMN reorientation impacts on an inter-subunit salt-bridge (K117-E96), which is stabilized in the light state, hence accounting for the observed decreased mobility. Based on these findings we propose an alternative mechanism for dimeric LOV photoactivation and intramolecular signal-relay, assigning a distinct structural role for the conserved “flipping” glutamine. The proposed mechanism is discussed in light of universal applicability and its implications for the understanding of LOV-based optogenetic tools.